Bauran Pemasaran Bibit Kelapa Sawit di PT Putra Bangka Mandiri (Jurnal Agribisnis dan Agrowisata, 2026)
Marketing Mix Oil PalmSeeds in PT Putra Bangka Mandiri. The marketing mix is a combination of four variables that are the core of the company's marketing system consisting of: product, price, distribution, and promotion. PT Putra Bangka Mandiri is the largest seed supply company in Bangka Belitung Province, this is an opportunity for the company in oil palm cultivation, therefore the company needs to know the marketing strategy to develop its business through marketing mix. The aim of the research is to determine the marketing mix PT Putra Bangka Mandiri. The research location was selected intentionally (purposively). The data types include primary and secondary. The data were collected by interview and documentation. Data were analyzed descriptively and qualitatively. Based on the research results, it was found that the marketing mix carried out by the company for the products used by PT Putra Bangka Mandiri has three varieties, namely Sriwijaya5, Simalungun and PPKS 540 but what will become a mainstay in 2020 is the Sriwijaya5 variety, with a total production of 100.000 seeds. Nurseries must meet the requirements after going through the two stages of the pre-nursery and main-nursery nursery proces. The selling price is determined based on the production costs used and the market price with a purchase price of IDR 45.000/seed. Distribution is carried out directly until the goods reach consumers without going through intermediaries. Promotion carried out by PT Putra Bangka Mandiri uses word of mouth promotion, namely communication from people such as friends, neighbors, co-workers and family members who are sources of messages and recipients of messages in non-commercial ways about a product, service or brand that can build consumer trust. The advice needed by PT Putra Bangka Mandiri can develop a variety of promotions such as online, seminars, events.
Keywords: marketing mix; seedlings; sj5